Cracking the Coronary Calcium with IntraVascular Lithotripsy - Debasish Das,; Debasis Acharya,; Jogendra Singh,; Tutan Das,; Subhas Pramanik, (Indian Journal of Case Reports, 2021)
Intervention in calcified coronaries remains a particular challenge as it is tough to crack the calcium with semi-compliant balloon dilatation. Coronary calcium is cracked with the non-compliant balloon, cutting balloon, scoring balloon, and rota ablation. Intravascular lithotripsy (IVL) has emerged now as a new modality to crack the coronary calcium and bring successful outcomes in coronary angioplasty. We present a case series of two cases where we cracked multi-vessel high dense coronary calcium with IVL and stented the coronary segments with drug-eluting stents to bring good angiographic results and Thrombolysis in Myocardial Infarction (TIMI) III flow.